A simple EU model in EViews - Fritz Breuss (Austrian Institute of Economic Research (WIFO), 2021)
Many studies with different methods (CGE models, DSGE models, structural gravity equations) have recently evaluated EU's Single Market. The problem with all these studies is that they use complex models with data sets which are not replicable. The aim of this paper is to develop a simple EU model which uses readily accessible data, and which is replicable in EViews. First the 10 equations macro model is used to evaluate Austria's EU membership since 1995. Then the same prototype model is applied to make a comparison of the integration effects of a selected number of EU Member States. Our simple EU model covers the essential economic effects of EU integration of EU's Single Market, the introduction of the Euro, and the following EU enlargements: increase in intra-EU trade, price reduction because of more competition, the impact of the net budget position vis à vis the EU budget, and lastly that on growth.
Keywords: F15; C51; O52; 330; European Integration; Model simulations; country studies